A low COMT activity haplotype is associated with recurrent preeclampsia in a Norwegian population cohort (HUNT2) - Roten, L.; Fenstad, M.; Forsmo, S.; Johnson, M.; Moses, Eric; Austgulen, R.; Skorpen, F. (2011)
The etiology of preeclampsia is complex, with susceptibility being attributable to multiple environmental factors and a large genetic component. Although many candidate genes for preeclampsia have been suggested and studied, the specific causative genes still remain to be identified. Catechol-O-methyltransferase (COMT) is an enzyme involved in catecholamine and estrogen degradation and has recently been ascribed a role in development of preeclampsia. In the present study, we have examined the COMT gene by genotyping the functional Val108/158Met polymorphism (rs4680) and an additional single-nucleotide polymorphism, rs6269, predicting COMT activity haplotypes in a large Norwegian case/control cohort (ncases= 1135, ncontrols= 2262). A low COMT activity haplotype is associated with recurrent preeclampsia in our cohort. This may support the role of redox-regulated signaling and oxidative stress in preeclampsia pathogenesis as suggested by recent studies in a genetic mouse model. The COMT gene might be a genetic risk factor shared between preeclampsia and cardiovascular diseases.